Recovery of zinc from the spent zinc-carbon dry cell batteries through pyrometallurgical route - Haque Khan, Majharul; Kurny, A.S.W. (Journal of Metals, Materials and Minerals, 2011)
Spent zinc-carbon batteries of all the five types (AAA, AA, C, D and 9V) were processed to recover zinc metal. All the components of the battery were separated, chemically analyzed and the anodic zinc parts were subjected to pyrometallurgical processing. Extraction of zinc was negligible when no fluxing agent was used. However, extent of recovery increased significantly when chloride salts: sodium chloride, calcium chloride and ammonium chloride were used as a fluxing agent. Among these, ammonium chloride gave the best result as flux. Using 10 %wt. of each flux, extraction of zinc was 90% for ammonium chloride, and around 75% for both sodium chloride and calcium chloride. A maximum 92% extraction of total zinc with purity over 99.5% could be obtained in presence of 12%wt. ammonium chloride flux by heating at 600°C for 10 minutes.